Lokakarya Pembuatan Tempe Sebagai Sarana Diplomasi Budaya dan Edukasi Pangan Fermentasi Tradisional Indonesia - Griselda Herman Natadiputri; Birgitta Narindri Rara Winayu; Dionysius Subali (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2026)
Tempeh, a traditional Indonesian fermented food, has been acknowledged for its high nutritional value. Besides, production of tempeh can be a potential practice-based educational medium. However, knowledge on tempeh fermentation remains limited, particularly among international participants. This study was aimed to implement a community engagement activity for fermented food education strategy through a tempeh-making workshop and to evaluate the improvement in knowledge and practical skills of international short-course participants. The program was conducted offline using interactive lectures, demonstrations, and hands-on practice sessions. Evaluation was performed using pre-test and post-test assessments along with direct observation during the activities. The results indicated a significant improvement in participants’ understanding of fermentation processes, microbial roles, and tempeh production stages. In addition, participants demonstrated enhanced practical skills and increased interest in further exploration of fermented foods. The activity also contributed to introducing tempeh as part of Indonesia’s culinary heritage to an international audience. Therefore, the tempeh workshop can serve as an effective educational strategy to enhance fermented food literacy while supporting food-based cultural diplomacy.